AmbiguItas Identitas daIam Akun Instagram Mahasiswa/i FakuItas IImu SosiaI dan IImu PoIitik Universitas Udayana - Savitri, Annastasia; Nugroho, Wahyu Budi; SastrI Mahadewi, Ni Made AnggIta (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
A dynamic society can’t be formed without communication, on the other hand even without society It is impossibie for individuais to deveioped communication. Instagram show that how someone trys to shep aiternate identity trough an account. This research was conducte to anaiyze the background and impiication of using an Instagram account by student of Udayana university.this reseach adopted quaiitative approaches descrptive to seek out that why individuais create to account Instagram to produce identity. This theory was seiected in this reseacrh was ambiguity identiy In new media theory by daniei chandier. There are sociai and poiitic facuity of Udayana university student who assesses the reai identity is in the first account and there is the opposite. Chandier though that a media can impIied In shifting the identity of a person appIies to students in Udayana university. The second Instagram account can impact other communities that can harm society at Iarge. Keywords: Instagram, ambIguty IdentIty, DanIeI ChandIer.